Chemical content of waste composting by black soldier fly (Hermetia illucens). Issue 1 (April 2021) - Widyastuti, R A D; Rahmat, A; Warganegara, H A; Ramadhani, W S; Prasetyo, B; Riantini, M
Abstract: Solid food waste from households and restaurants in urban areas currently be a severe problem. Mismanagement of solid food waste can promote disease. Black Soldier Fly larvae were known as new composting technology because they fast in the composting process. To decrease the volume of solid food waste that Black Soldier Fly larvae can be applied. This research aims to study the chemical content of the compost from composting by Black Soldier Fly larvae. The results show that the C-organic compost content is 18, 37%, Total Nitrogen is 1.45%, Total Phosphor is 1.58%, and the pH is 6.8, C/N ratio is 12.66. Total Nitrogen, Total Phosphor, C/N ratio, and pH have fulfilled the requirements of the National compost standard of Indonesia (SNI). So, Compost from Black Soldier Fly larvae has high potential as a standard compost.